1993
DOI: 10.1093/ajh/6.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Effect of Losartan, a Nonpeptide Angiotensin II Receptor Antagonist, in Essential Hypertension

Abstract: We examined the chronic effects of losartan (DuP 753), a novel orally active angiotensin II receptor antagonist, on blood pressure and renal function in eight hospitalized patients with essential hypertension. After a control period of 1 week, losartan was administered orally once a day for 2 to 4 weeks in increasing doses of 12.5, 25, 50, and 100 mg, until blood pressure in the supine position decreased more than 20 mm Hg (systolic) and 10 mm Hg (diastolic) (or 13 mm Hg in mean blood pressure). The average do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…3 Clinical trials have demonstrated that losartan potassium given alone lowers blood pressure (BP) and is well tolerated in longterm trials in patients with essential hypertension. 4 Despite the efficacy of losartan potassium or other monotherapy agents such as hydrochlorothiazide (HCTZ), some patients with more resistant forms of hypertension may require concomitant antihypertensive therapy to control their BP. 5 The purpose of this 3-year trial was to assess the long-term effects of ACE inhibitors (enalapril) vs selective AT1 receptor blockade (losartan) on reactive cardiac hypertrophy and on renal function in patients with mild to moderate essential hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…3 Clinical trials have demonstrated that losartan potassium given alone lowers blood pressure (BP) and is well tolerated in longterm trials in patients with essential hypertension. 4 Despite the efficacy of losartan potassium or other monotherapy agents such as hydrochlorothiazide (HCTZ), some patients with more resistant forms of hypertension may require concomitant antihypertensive therapy to control their BP. 5 The purpose of this 3-year trial was to assess the long-term effects of ACE inhibitors (enalapril) vs selective AT1 receptor blockade (losartan) on reactive cardiac hypertrophy and on renal function in patients with mild to moderate essential hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…For example, telmisartan has been reported to be beneficial for glucose and lipid metabolism (13,14), and losartan to be beneficial for uric acid reduction (6)(7)(8)(9)(10). The present study demonstrated that PRT may be of benefit in cholesterol and uric acid metabolism, although we can not exclude the possibility that the reduction of uric acid and cholesterol may be affected by diet, because we did not control diet during the study period.…”
Section: Discussionmentioning
confidence: 55%
“…Losartan has been reported to decrease the serum uric acid level in normal volunteers (32) and in hypertensive patients (33). Losartan inhibits the uric acid transporter (URAT1) and thus decreases the serum uric acid level, while other ARBs only inhibit URAT1 weakly (34,35).…”
Section: Discussionmentioning
confidence: 99%